DAMPAK PEMANASAN GLOBALPENGOLAHAN HASIL PERIKANAN MENGGUNAKAN METODELIFE CYCLE ASSESSMENT (LCA): ANALISIS GATE-TO-GATE - Intan Sofiah, Mohamad Yani dan Andes Ismayana (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
Life cycle assessment (LCA) is widely applied method ofquantifying the environmental impact on products and processes. One of the most application is LCA in fishery industry. This research was conducted in fishery processing industry in Cirebon Jawa Barat. The methodology of LCA based on ISO 14040 framework which consists of four stages such as goal and scope definition, inventory analysis, impact assessment, and interpretation and improvement analysis. The scope of this LCA research is production process of industry. By calculating using Intergovernmental Panel on Climate Change (IPCC) equation, industry of fisheries product processing in this study emitted green house gases (GHG) as much as 0.56 g for fish product and 1.62 g for crab product. The alternatives to reducing environmental impacts are to change the refrigerant used, which can reduce the GHG emissions as much as 68.37% and adjusting the water usage, which can reduce the GHG emissions as much as 6.09%.Keywords: fishery industry,life cycle assessment, GHG emissions